Impact of Antimicrobial Stewardship Program on Vancomycin Usage: Costs and Outcomes at Hospital for Tropical Diseases in Ho Chi Minh City, Vietnam - Nguyen-Thi HY; Nguyen DA; Huynh PT; Le NDT (Dove Medical Press, 2021)
Hai-Yen Nguyen-Thi,1 Duy-Anh Nguyen,1 Phuong-Thao Huynh,2 Nguyen Dang Tu Le1 1Department of Pharmaceutical Administration, University of Medicine and Pharmacy at Ho Chi Minh City, Ho Chi Minh City, Vietnam; 2Department of Pharmacy, Hospital for Tropical Diseases, Ho Chi Minh City, VietnamCorrespondence: Hai-Yen Nguyen-ThiDepartment of Pharmaceutical Administration, Faculty of Pharmacy, University of Medicine and Pharmacy at Ho Chi Minh City, 41 Dinh Tien Hoang Street, Ho Chi Minh City, VietnamTel +84 938769626Email haiyen@ump.edu.vnBackground: Nowadays, with the emergence of vancomycin-resistant strains, the clinical use of vancomycin has been followed closely by applying the antimicrobial stewardship program (ASP) to enhance effectiveness in treatment and reduce cost burden for patients.Methods: A descriptive cross-sectional study at the Hospital for Tropical Diseases was conducted to assess the inpatient status assigned to intravenous vancomycin and factors associated with the cost of treatment during two periods of implementing ASP, which were i) from April 1, 2016 to March 31, 2018 (previous ASP-pASP) and ii) from June 1, 2018 to March 31, 2020 (new ASP-nASP).Results: Among 1375 patients who met the sampling criteria, there were 601 and 774 patients in pASP and nASP, respectively. The rate of no improvement/mortality in the pASP was higher than that in nASP (37.10% vs 25.98%, p < 0.05). The proportion of patients with two or more infection episodes in nASP is lower than that in pASP (9.83% vs 18.64%, p< 0.05). Besides, nASP has higher length of therapy (LOT) and higher day of therapy (DOT). The average treatment cost in the pASP is higher than that in the nASP, 1891.22 (95% CI, 1713.46– 2068.98) USD vs 1775.55 (95% CI, 1576.22– 1974.88) USD. There are seven factors (p< 0.05) that associate with the total cost of treatment (age, number of infection episodes, length of stay, discharge status, clinical department, LOT, DOT) in pASP. On the other hand, the nASP has five factors (p< 0.001), in which the log(LOT) and age are not as statistically significant (p=0.5127 and 0.3852, respectively) as in the pASP model.Conclusion: The implementation and improvement of the ASP at the Hospital for Tropical Diseases have initially shown benefits for patients using intravenous vancomycin. Specifically, the ASP helps to reduce treatment costs, improve patient outcomes, reduce length of stay and decrease the average daily dose of vancomycin.Keywords: antimicrobial stewardship program, vancomycin, Hospital for Tropical Diseases, Vietnam, treatment costs, outcomes